Biomechanical Analysis of a Hip Prosthesis Using a Finite Elements - Martínez-Valencia, Ana Beatríz; Hernández-Romero, Karina; Béjar-Gómez, Luis; Villagómez-Galindo, Miguel (Revista Mexicana de Ingenieria Biomedica, 2020)
This paper shows a biomechanical analysis of a hip prosthesis under conditions of loads associated with daily activities. For which it compared three metallic materials for the manufacture of a customized prosthesis from medical images, it was used cloud platforms with computer-aided design and finite element analysis. Two models of prosthesis one hollow and the other one solid using parametric spline curves were designed and analyzed. The biomechanical analysis required a mesh size consisting of 2’537,684 tetrahedral elements and 471,335 nodes to study seven cases of postures for a person weighing 75 kg. These cases were analyzed based on 316L stainless steel, Ti-6AL-4V alloy, and another L-605 alloy. It was observed that with activities such as jogging, climbing and descending stairs, materials 316L, and L-605 present the risk of plastic deformation and even fracture. The results show that the most suitable material for the manufacture of this type of prosthesis is the Ti-6Al-4V, which allows us to make both solid and hollow models. Assuming this last material is saved and improves the prosthesis lightness.